2020
DOI: 10.2478/ats-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of lack of credit access among indigenous vegetable producers in Nigeria: Implications for policy interventions

Abstract: In this study we assessed the determinants of lack of credit access among the Indigenous Vegetables (IVs) farmers based on primary data collected in a cross-sectional survey. Using descriptive statistics and logistic regression analysis, the results revealed that more females were involved in the indigenous vegetable production with average age of 40 years, seven household members, eight years of formal education and cultivating 0.76 acre of land. Only 8 % had access to credit and 76 % did not have contact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…This is agreed in a previous study, which stated that member farmers were more aware of the latest technology and practices (Adeoye, 2020). Tanimonure et al (2020) suggested the vegetable farmers to engage in cooperative societies or form active groups. As a result, member farmers could take advantage of production technology and market information.…”
Section: Factors Motivating Farmers To Adopt the Commercial Vegetable...mentioning
confidence: 99%
“…This is agreed in a previous study, which stated that member farmers were more aware of the latest technology and practices (Adeoye, 2020). Tanimonure et al (2020) suggested the vegetable farmers to engage in cooperative societies or form active groups. As a result, member farmers could take advantage of production technology and market information.…”
Section: Factors Motivating Farmers To Adopt the Commercial Vegetable...mentioning
confidence: 99%